Maternal perceptions and preventive behaviors in school-age children during the pandemic - Lut Fika Daru Azmi; Fitri Haryanti; Lely Lusmilasari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Although COVID-19 is no longer at its peak, its influence on preventive practices remains relevant, especially for families with school-age children. In children, the incident is not as high as in adults, but is increasing all the same. The preventive behaviour of children is strongly linked to that of the mother. Cognitive reinforcement (perception) is a factor that influences behaviour. In this case, the recognition is divided into four parts: perceived susceptibility, severity, benefits, and barriers. Purpose: To elucidate the relationship between perception and the behavior of mothers who have school-age children related to COVID-19 prevention. Method: We adopted a cross-sectional design with a sample of 110 mothers who have school-age children (8–11 years) using the consecutive sampling technique. Moreover, we questionnaire to measure the perceptions of these mothers in COVID-19 prevention, the result of a modified ARI-Questionnaire and a questionnaire on Mother's Behavior in Prevention of COVID-19. Data analysis was performed using Spearman Rho'. Results: There was a relationship between the perception and behavior of mothers related to COVID-19 prevention as evidenced by a p = 0.001 with a close relationship (r) of 0.194. Other factors that influenced the behavior of mothers in COVID-19 prevention included the educational level of the mother, and the number of the childrens. Conclusion: Changes in mothers’ behavior is influenced by several factors: perception, number of children, income and highest educational level of the mother, and the gender of the child. COVID-19 prevention will be more optimal if the perception of the mother is good, and the mother has a low perception of barriers.